2019
DOI: 10.1186/s13059-019-1783-3
|View full text |Cite
|
Sign up to set email alerts
|

AlleleAnalyzer: a tool for personalized and allele-specific sgRNA design

Abstract: The CRISPR/Cas system is a highly specific genome editing tool capable of distinguishing alleles differing by even a single base pair. Target sites might carry genetic variations that are not distinguishable by sgRNA designing tools based on one reference genome. AlleleAnalyzer is an open-source software that incorporates single-nucleotide variants and short insertions and deletions to design sgRNAs for precisely editing 1 or multiple haplotypes of a sequenced genome, currently supporting 11 Cas proteins. It a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In a recent study, AlleleAnalyzer, a bioinformatic tool was reported to target SNPs by obtaining sequences data from the 1,000 Genomes project. By utilizing disease-associated haplotypes, AlleleAnalyzer designs allele-specific dual gRNAs (Keough et al, 2019). Scott and Zhang (2017) and Lessard et al (2017) also developed bioinformatic tools to design gRNAs that target conserved genomic loci to avoid gRNA incompatibility due to genetic variations.…”
Section: Snp-derived Pammentioning
confidence: 99%
“…In a recent study, AlleleAnalyzer, a bioinformatic tool was reported to target SNPs by obtaining sequences data from the 1,000 Genomes project. By utilizing disease-associated haplotypes, AlleleAnalyzer designs allele-specific dual gRNAs (Keough et al, 2019). Scott and Zhang (2017) and Lessard et al (2017) also developed bioinformatic tools to design gRNAs that target conserved genomic loci to avoid gRNA incompatibility due to genetic variations.…”
Section: Snp-derived Pammentioning
confidence: 99%
“…Just as we just finished the AsCRISPR implementation, another software termed AlleleAnalyzer was published, aiming to identify optimized personalized and allele-specific sgRNAs. 52 AlleleAnalyzer also leverages patterns of shared genetic variation across thousands of publicly available genomes to design sgRNA pairs that will have the greatest utility in large populations. 52 However, the difference is that as a web tool, AsCRISPR can process either user-identified sequences or SNP numbers, which is more likely to be demand driven for research studies and clinical therapeutics.…”
Section: Comparison With Similar Serversmentioning
confidence: 99%
“…52 AlleleAnalyzer also leverages patterns of shared genetic variation across thousands of publicly available genomes to design sgRNA pairs that will have the greatest utility in large populations. 52 However, the difference is that as a web tool, AsCRISPR can process either user-identified sequences or SNP numbers, which is more likely to be demand driven for research studies and clinical therapeutics. Moreover, AsCRISPR only outputs single sgRNAs instead of pairs of sgRNAs, although users may also freely use AsCRISPR to design another sgRNA manually to make a sgRNA pair.…”
Section: Comparison With Similar Serversmentioning
confidence: 99%
“…Although good online tools are available for identification of CRISPR DNA targets, which have popularized genome editing, their use is limited to a restricted list of genomes [1][2][3][4][5][6], sometimes corresponding to less than ten species [7,8]. Even Breaking-Cas [9], a free online tool which currently offers more than 1600 genomes, lacks the flexibility to easily incorporate unpublished genomes or contemplate genomes of populations with allelic variants -an issue partially addressed by AlleleAnalyzer for the human genome [10]. Several command-line tools present more flexibility incorporating any genome provided by users, like sgRNA-cas9 [11] or CRISPRseek [12].…”
Section: Introductionmentioning
confidence: 99%